Isolation of High‐Quality Total RNA from Small Animal Articular Cartilage for Next‐Generation Sequencing. Issue 3 (7th March 2023) - Takács, Roland; Póliska, Szilárd; Juhász, Tamás; Barna, Krisztina B.; Matta, Csaba
Abstract: Articular cartilage is characterized by a low density of chondrocytes surrounded by an abundant extracellular matrix (ECM) consisting of a dense mixture of collagens, proteoglycans, and glycosaminoglycans. Due to its low cellularity and high proteoglycan content, it is particularly challenging to extract high‐quality total RNA suitable for sensitive high‐throughput downstream applications such as RNA sequencing (RNA‐Seq). Available protocols for high‐quality RNA isolation from articular chondrocytes are inconsistent, resulting in suboptimal yield and compromised quality. This poses a significant difficulty in the application of RNA‐Seq to study the cartilage transcriptome. Current protocols rely either on dissociation of cartilage ECM by collagenase digestion or pulverizing cartilage using various methods prior to RNA extraction. However, protocols for cartilage processing vary significantly depending on the species and source of cartilage within the body. Protocols for isolating RNA from human or large mammal (e.g., horse or cattle) cartilage samples are available, but this is not the case for chicken cartilage, despite the species being extensively used in cartilage research. Here, we present two improved RNA isolation protocols based on pulverization of fresh articular cartilage using a cryogenic mill or on enzymatic digestion using 1.2% (w/v) collagenase II. Our protocols optimize the collection and tissue processing steps to minimize RNA degradation and enhance RNA purity. Our results show that RNA purified from chicken articular cartilage using these methods has appropriate quality for RNA‐Seq experiments. The procedure is applicable for RNA extraction from cartilage from other species such as dog, cat, sheep, and goat. The workflow for RNA‐Seq analysis is also described here. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Extraction of total RNA from pulverized chicken articular cartilage Alternate Protocol : Extraction of total RNA from collagen‐digested articular cartilage Support Protocol : Dissection of chicken articular cartilage from the knee joint Basic Protocol 2 : RNA sequencing of total RNA from chicken articular cartilage